Cloning and sequencing of Escherichia coli ubiC and purification of chorismate lyase. - Nichols, B P (1992)
In Escherichia coli, chorismate lyase catalyzes the first step in ubiquinone biosynthesis, the conversion of chorismate to 4-hydroxybenzoate. 4-Hydroxybenzoate is converted to 3-octaprenyl-4-hydroxybenzoate by 4-hydroxybenzoate octaprenyltransferase. These two enzymes are encoded by ubiC and ubiA, respectively, and have been reported to map near one another at 92 min on the E. coli chromosome. We have cloned the ubiCA gene cluster and determined the nucleotide sequence of ubiC and a portion of ubiA. The nucleotide sequence abuts with a previously determined sequence that encodes a large portion of ubiA. ubiC was localized by subcloning, and overproducing plasmids were constructed. Overexpression of ubiC allowed the purification of chorismate lyase to homogeneity, and N-terminal sequence analysis of chorismate lyase unambiguously defined the beginning of the ubiC coding region. Although chorismate lyase showed no significant amino acid sequence similarity to 4-amino-4-deoxychorismate lyase (4-amino-4-deoxychroismate----4-aminobenzoate), the product of E. coli pabC, chorismate lyase overproduction could complement the growth requirement for 4-aminobenzoate of a pabC mutant strain. Of the several enzymes that convert chorismate to intermediates of E. coli biosynthetic pathways, chorismate lyase is the last to be isolated and characterized.